The Osage of the Flint Hills - Kathleen Auschwitz (Symphony in the Flint Hills, 2014)
Near Rosalia in east-central Butler County, there is a trail that crosses from east to west. It intersects with the California Trail and the Texas Cattle Trail. It passes by the town of Towanda, which stands on the edge of what was once the buffalo range.
Keywords: Towanda; Smithsonian American Art Museum; Indians; Osage Indians; Osage Nation; Flint Hills; Butler County; trail; warriors; Homstead Act of 1862; prairie; Nebraska-Kansas Act; tribes; bison; buffalo; Towanda Springs; Osage Trail; Osage; water; ancestral; ancestry; Civil War; Cherokee; Choctaw; Creek; Confederacy; Union; Wichita; families